Применение статистических моделей в инженерии качества процессов производства программных систем - Matveeva, L.Е.; Gorislavets, T.N. (Інститут програмних систем НАН України, 2015)
Ability to manage performance of software engineering processes contributes to the quality of developed software systems. By analyzing the processes’ models it is possible to gain deeper insight into the nature of the processes, control and improve them, and therefore enhance the software product quality. This paper presents the examples of the statistical process control methods use, namely Process Capability Baselines establishment and their analysis by means of control charts, and development of Process Performance Model which is used to predict the value of process performance measure.